The Glucose Challenge Test for Screening of Gestational Diabetes - Shrestha, A; Chawla, C D (Kathmandu University Medical Journal, 2012)
Background The frequency of gestational diabetes mellitus (GDM) is 0.6% -15% of pregnant woman. The modern trend towards the delay starting family is the main factor responsible for increase prevalence of GDM. This condition is associated with the adverse effect on mother and fetus, so it is important to find out the GDM by screening of all the pregnant women. Objective To observe the feasibility of using the 50g GCT for all pregnant women attending Dhulikhel Hospital, Obstetric OPD. To determine the incidence of gestational diabetes in the population and to observe the maternal and fetal outcome among those having an elevated GCT level and gestational diabetes. Methods A prospective and analytical study of 1598 pregnant women booked and delivered between June 2009and August 2010. Glucose challenge test (GCT) performed by using 50gm glucose and diagnosis of gestational diabetes performed by using the Carpenter Coustan Criteria. Pregnancy outcomes were assessed by the gestation and mode of delivery. Similarly, neonatal outcomes assessed in terms of birth weights, APGAR scores, congenital abnormalities, hyperbilirubinaemia, hypoglycaemia or respiratory distress syndrome. Results The detected incidence of gestational diabetes was 0.75%. With the threshold plasma glucose level at140 mg/ dl, 198 women needed to undergo the 100g oral glucose tolerance test and 12 women had gestational diabetes. The diagnostic yield was 6.06%. Perinatal outcome was similar to the rest of the women with normal glucose challenge test. Conclusions The 50g GCT is feasible and also helps to find out GDM. It is easy, user friendly, cheap and convenient for screening purpose. DOI: http://dx.doi.org/10.3126/kumj.v9i2.6282  Kathmandu Univ Med J 2011;9(2):22-25